Chapter Leonardo a Faenza? Precisazioni e ipotesi a margine della spedizione borgiana in Romagna - PASCALE GUIDOTTI MAGNANI, DANIELE (Territori, 2023)
During Cesare Borgia's expedition in Romagna, Leonardo da Vinci designed many public works for Cesena but it is still unclear if he worked in other cities of the region. In particular, a possible passage through Faenza should be investigated. Some scholars think that a drawing of Leonardo's notebook L (Paris, Institut de France) could be a representation of Faenza cathedral, but this attribution is disputed. Moreover, in Faenza's countryside there are some original castles with hexagonal, rhomboid or ogival plan. It is not clear if Leonardo knew these buildings, perhaps even before the Borgian military campaign.